2013
DOI: 10.1115/1.4024765
|View full text |Cite
|
Sign up to set email alerts
|

Gas-Filled Encapsulated Thermal-Acoustic Transducer

Abstract: A new model for a gas-filled encapsulated thermal-acoustic transducer, which uses newly devised carbon nanotube (CNT) thin film is developed and the exact and approximate solutions are derived. A comparison between theoretical prediction and experimental data is presented and excellent agreement is reported. The frequency response for this acoustic transducer is investigated and the acoustic response of as a function of window–thin-film distance of the encapsulated transducer is discussed. An optimal distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Since carbon nanostructured materials possess the thermal properties required [7], extensive research has been conducted on their potential to emit sound via the thermoacoustic effect, such as carbon nanotubes (CNTs) [6][7][8][9][10][11][12][13][14][15][16][17][18][19], 2D graphene [20][21][22][23][24][25], and 3D graphene (3D-C) [26,27]. These studies demonstrate the influence of frequency, input power, microstructure and backing on the acoustics performance of the carbon nanostructured materials, obtained from the conducted experiments.…”
Section: Introductionmentioning
confidence: 97%
“…Since carbon nanostructured materials possess the thermal properties required [7], extensive research has been conducted on their potential to emit sound via the thermoacoustic effect, such as carbon nanotubes (CNTs) [6][7][8][9][10][11][12][13][14][15][16][17][18][19], 2D graphene [20][21][22][23][24][25], and 3D graphene (3D-C) [26,27]. These studies demonstrate the influence of frequency, input power, microstructure and backing on the acoustics performance of the carbon nanostructured materials, obtained from the conducted experiments.…”
Section: Introductionmentioning
confidence: 97%
“…39,40 This continuity is automatically verified if we adopt the matrix form given in Eq. (42). By imposing the continuity of the variables at interfaces between layers we found…”
Section: Transfer Matrix Methods With N Cylindrical Layersmentioning
confidence: 98%
“…Here subscript 2 indicates parameters that are related to the substrate. The thermal diffusion length of thermal wave is ffiffiffiffiffiffiffiffiffiffiffiffiffiffi 2a 2 =u p [4,21,22,25], hence thermally-thick condition is readily satisfied for the substrate. By using no reflection boundary condition, the thermal wave sharply attenuates before arriving at the back of substrate.…”
Section: Thermal Fieldmentioning
confidence: 97%
“…However, the influence of thermal loss and conductor HCPUA was not included in their analysis [13]. Recently, Lim et al [6] and Tong et al [22] reported accurate analytical solutions for thermoacoustic radiation from a suspended (CNT) thinfilm and a gas-filled encapsulated thermoacoustic transducer, respectively. Their analytical solutions were compared with published experimental measurements and excellent agreements were achieved.…”
Section: Introductionmentioning
confidence: 97%